Alterations in fibrin formation and fibrinolysis in early onset-preeclampsia: Association with disease severity. (October 2019) - Haire, Gordon; Egan, Karl; Parmar, Kiran; McKinnon, Tom; Monteith, Cathy; O'Connor, Hugh; Kevane, Barry; Maguire, Patricia; Szklanna, Paulina B.; Galligan, Marie; Donnelly, Jennifer C; Allen, Seamus; et al.
Abstract: Objective: ; Early-onset preeclampsia is a rare pregnancy-specific disorder associated with significantly increased maternal and fetal morbidity and mortality. Whilst it is known that even normotensive pregnancies are associated with changes in clot formation and dissolution, the nature of how these changes differ in those with early onset preeclampsia has not been well established. We sought to evaluate parameters of fibrin formation and fibrinolysis in individuals with early onset preeclampsia in comparison to both pregnant and non-pregnant controls. Furthermore, such parameters were correlated with markers of disease severity in this patient cohort, including the presence of multiorgan involvement, the rate of disease progression and the extent of the anti-angiogenic state in this condition. Study design: ; Patients with early onset preeclampsia (N = 20) and both pregnant (N = 16) and non -pregnant (N = 16) controls were recruited from the cohort at a large urban maternity hospital which saw over 15, 000 deliveries during the study period. Platelet poor plasma was prepared from collected whole blood and analysed for parameters of fibrin formation and fibrinolysis (lagtime to and rate of fibrin formation; PAI-1; PAI-2; D-dimer; plasmin-antiplasmin; tPA) in addition to markers of angiogenesis (sFLT-1; Endoglin) using commercially available specific immunoassays. Results: ; The maximum rate of fibrin formation as well as PAI-1, PAI-2 and D-dimer levels were all significantly increased in those with early onset preeclampsia and pregnant controls when compared to non-pregnant controls without significant differences between the 2 former groups. Plasmin-antiplasmin levels were significantly reduced in a similar manner. tPA levels were significantly elevated in EOP compared to both pregnant and non-pregnant controls. EOP was associated with significantly increased anti-angiogenic factors (sFLT-1; Endoglin) when compared to both pregnant and non-pregnant controls. Conclusion: ; Markers of fibrin formation and fibrinolysis are significantly alerted in early onset preeclampsia; furthermore, certain markers correlate with disease severity in this patient cohort.